HESTIA PROJECT'S EFFECTIVENESS IN OVERCOMING SHAM MARRIAGES IN IRELAND (2015-2016) - Merry Cristin; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Exploitative sham marriages have been identified as a form of human trafficking on the territory of the European Union. In the case of sham marriages, Ireland is the destination country for marriages by other EU citizens with third party nationals with the aim of obtaining residence permits. The problem with this phenomenon is that it is not yet known how the process of exploitative sham marriages is and its relationship to human trafficking. To deal with this problem, the Directorate General of Home Finance of the European Commission (EC) “Prevention of and Fight Against Crime Program” formed the HESTIA Project which aims to create a common understanding of sham marriage as a form of human trafficking by providing precise definitions and initiating comprehensive actions to prevention. This study uses qualitative research methods, with data collection techniques through the analysis of documents, books and journals. By conducting an analysis using the indicators of the theory of effectiveness of the international regime by Underdal which the author borrowed in this study, the HESTIA Project succeeded in meeting the effectiveness indicators such as problem type, problem solving capacity and level of collaboration. Therefore, the HESTIA Project is effective in tackling sham marriages in Ireland. Keywords: Sham Marriage, HESTIA Project, Effectiveness of International Cooperation, Ireland.